Flyposter graffiti and the change in a Sydney streetscape during the time of COVID-19. Issue 2 (15th March 2021) - Hicks, Megan
Abstract : Unauthorised posters stuck on public walls and street furniture contribute to a sense of place in ways that transcend their usual characterisation as unwanted graffiti and visual pollution. They are a common sight in Newtown-Enmore, a destination precinct of Sydney, Australia. In September-October 2020, at a time when COVID-19 restrictions were easing, I found that many of the fly-posters in this district related to COVID-19 either directly or indirectly. While some advertised entertainment venues, most were political, their messages ranging through leftist, anarchist and conspiracy theorist propaganda. This visual essay documents not only the posters themselves but also evidence of public engagement with them. It captures a two-way battle that was being waged, with people ripping some posters down or writing over them, and in return, bill posters pasting up new notices condemning the defacers. The effect of this heightened flyposter activity was to bring about change to the local streetscape in a remarkable but subtle way.